The Effect of Different Levels of Minerals and Vitamins Premixes on Performance of Laying Hens fed by Wheat and Corn Base Diets - A. Nobakht (پژوهشهای علوم دامی ایران, 2013)
This experiment was conducted to evaluate effects of different levels of mineral and vitamin premixes with wheat and corn base diets on performance and egg traits of laying hens. Experiment carried out as 2*5 factorial include wheat and corn base diets and 5 levels of minerals and vitamin premixes (0, 0.25, 0.35, 0.45 and 0.55 percentage) in a completely randomized design with 360 Hi-Line (W36) laying hens from 65 to 77 weeks in 10 treatments, 3 replicates and 12 hens in each replicate for 12 weeks. The results showed that diets composition, level of mineral and vitamin premixes, and interaction between them significantly affected the performance and egg traits of laying hens (P